Environmental Bacteriophages of the Emerging Enterobacterial Phytopathogen, Dickeya solani, Show Genomic Conservation and Capacity for Horizontal Gene Transfer between Their Bacterial Hosts - Day, Andrew; Ahn, Jiyoon; Fang, Xinzhe; Salmond, George P. C. (Frontiers in Microbiology, 2017)
Dickeya solani is an economically important phytopathogen widespread in mainland Europe that can reduce potato crop yields by 25%. There are no effective environmentally-acceptable chemical systems available for diseases caused by Dickeya. Bacteriophages have been suggested for use in biocontrol of this pathogen in the field, and limited field trials have been conducted. To date only a small number of bacteriophages capable of infecting Dickeya solani have been isolated and characterised, and so there is a need to expand the repertoire of phages that may have potential utility in phage therapy strategies. Here we describe 67 bacteriophages from environmental sources, the majority of which are members of the viral family Myoviridae. Full genomic sequencing of two isolates revealed a high degree of DNA identity with Dickeya solani bacteriophages isolated in Europe in the past five years, suggesting a wide ecological distribution of this phage family. Transduction experiments showed that the majority of the new environmental bacteriophages are capable of facilitating efficient horizontal gene transfer. The possible risk of unintentional transfer of virulence or antibiotic resistance genes between hosts susceptible to transducing phages cautions against their environmental use for biocontrol, until specific phages are fully tested for transduction capabilities.